Research on collaborative optimization of fuel cell tractor transmission system and control strategy parameters - Xu, Liyou; Chen, Shixun; Zhang, Junjiang; Liu, Mengnan; Wu, Yiwei; Yan, Xianghai (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The distributed fuel cell tractor is a new type of power tractor. The transmission system and control strategy parameters affect the energy utilization efficiency of the entire machine. There is currently no research in this area. In order to solve the problem of low energy utilization of the whole machine of distributed dual-motor-driven hydrogen fuel cell tractor, a cooperative optimization method is proposed, based on particle swarm optimization (PSO) algorithm for the parameters of the transmission system and energy-saving control strategy of distributed dual-motor-driven hydrogen fuel cell tractor. According to the tractor dynamics analysis and equivalent hydrogen consumption theory, a fuel cell tractor transmission parameter-equivalent hydrogen consumption model is established, The wheel-side transmission ratio and the upper and lower threshold values of the hydrogen fuel cell working power are taken as control variables, and the minimum equivalent hydrogen consumption is taken as the optimization goal, the optimization method is simulated and tested based on the MATLAB simulation platform. The results show that under plowing conditions, compared with the rule-based control strategy, the proposed collaborative optimization method of the fuel cell tractor transmission system and control strategy parameters can reasonably control the operating status of the fuel cell and the power battery, ensure that the fuel cell works in a high-efficiency range, enhance the overall performance of the fuel cell system, and control the power battery state of charge (SOC) to remain in a reasonable range. The tractor equivalent hydrogen consumption is reduced by 7.84%.